The effects of the first wave of COVID-19 restrictions on physical activity: a longitudinal study from “step into health” program in Qatar - Al-Mohannadi, Abdulla S.; Farooq, Abdulaziz; Salman, Ahmad; Ghram, Amine; Al-Harahsheh, Sanaa T.; Majed, Lina; Sayegh, Suzan; Cardinale, Marco (Frontiers in Public Health, 2024)
The COVID-19 pandemic led to restrictions that prevented physical activity in public places. This study sought to conduct a comprehensive longitudinal analysis of how lockdown policies in an Arabian Gulf country influenced the patterns of physical activity during first wave. Methods: In a longitudinal study design, members of the ongoing "Step into health" community-based health promotion program who provided valid pedometer data from January to August 2020, covering pre, during and post-covid first wave period met the inclusion criteria. Results: 420 (76.7% men, 13.8% ≤40 years) were included in the study. Overall, significant decline in daily step counts was recorded (-1130±SE302) after the implementation of lockdown policies (p<0.001). When the restrictions were removed, the steps per day were still lower compared to pre-covid for men (-910±SE610, p=0.017) and among individuals with normal BMI (-1304±SE409, p=0.004). The lockdown in Qatar did not significantly affect women and individuals with obesity who already had lower daily steps pre-covid. Discussion: The present study confirms immediate decline in daily steps imposed indirectly through the COVID-19 lockdown measures. Participants with higher physical activity levels pre-covid experienced significant decline in step count during and even after restrictions were uplifted.